Risk factors associated with postoperative delirium in elderly patients undergoing hip surgery - Liu, Xiao-Hong; Zhang, Qing-Fu; Liu, Ying; Lu, Qing-Wang; Wu, Jian-Hua; Gao, Xiao-Hua; Chen, Zhi-Yuan (Frontiers in Psychiatry, 2023)
Objective We retrospectively analyzed the occurrence of postoperative delirium following hip surgery and the associated risk factors. The aim was to establish a clinical foundation for preventing postoperative delirium after hip surgery. Methods We retrospectively selected elderly patients who had hip surgery at our hospital between January 2022 and August 2022. We included patients who experienced delirium in the observation group and those who did not encounter delirium in the control group. We then proceeded to compare various indicators among these two groups of patients. Results We analyzed a total of 97 cases of hip surgery, and among them, 32 cases experienced postoperative delirium, resulting in an incidence rate of 32.9%. Various factors were found to be linked to the development of postoperative delirium, including age, height, gender (male), preoperative erythrocyte sedimentation rate (ESR), postoperative ESR, preoperative lactate levels, pain scores on the first day after surgery, type of surgical procedure, and the occurrence of delirium in the post-anesthesia care unit (PACU delirium). Additionally, it was observed that 75% of patients who had PACU delirium also experienced postoperative delirium. Conclusion Postoperative delirium in patients who have hip surgery had an incidence rate of 32.9%. This phenomenon is linked to various factors that pose a risk, such as the patient age, height, gender, preoperative ESR levels, postoperative ESR levels, preoperative lactate levels, pain scores on the day following surgery, and the specific surgical procedure performed. The likelihood of experiencing delirium increases by 12% for every additional 10 years in patient age. Additionally, the occurrence of delirium in the PACU is a strong indicator of the likelihood of experiencing postoperative delirium.